Large ovarian cyst in children: differential diagnostic problem – case report - Mirko Raković; Zoran Rakonjac; Mirko Šatara; Slavko Grbić (Биомедицинска истраживања, 2014)
Introduction: . Ovarian cysts occur when a portion of the ovary is filled with liquid. The most common cysts are functional, and their size is usually between 2 and 6 cm, although cases of the large-size cysts have been described, as well. Case Outline . This paper reports a case of a 16-year-old girl admitted with a large tumorous mass of unclear etiology in the abdomen. Ten months prior to her admission she had noticed that ’’her stomach was growing’’. She had no subjective difficulties. Prior to hospitalisation she complained of having diffi culties moving and of tiredness when being more active. According to laboratory findings and radiological examinations (US and CT of abdomen) it was not possible to establish the origin of the tumorous mass, i.e. the attachment to any abdominal organ. Based on our experience, we assumed that this was either mesenteric or ovarian cyst. Laparotomy was performed, and based on surgical and pathohistological reports, a large serous cyst of the left ovarium size 35.65 cm X 14.90 cm containing 10.5 l of liquid, was established. No complications were detected during the surgical and post-surgical procedures. Conclusion: . In differential-diagnosis of cystic lesions of the ovary visual diagnostic methods (US, CT, MRI) may be useful although often only after surgery and histological verification of cysts, definitive diagnosis can be set.
Keywords: children; ovarian cysts; diagnosis; treatment